2019
DOI: 10.2503/hortj.okd-161
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High Temperature Treatment on the Sprouting and Elongation Rate of Asparagus Spears

Abstract: In this study, we investigated the effect of high temperature on spear sprouting and elongation in asparagus to explore new approaches to control the harvest period in asparagus production. Four-year-old rootstocks of 'UC157' were grown in chambers in the dark at 30°C (30°C treatment), 34°C (34°C treatment), 38°C (38°C treatment), and 42°C (42°C treatment) for 14 days, and then at 25°C for 18 days. In the 42°C treatment, no spear sprouting was detected, and all rootstocks died. During the high temperature peri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Growth rates of daily elongation of asparagus shoots increase between minimum temperatures 7-10 ∘ C to maximum of 25-30 ∘ C and when the shoot is longer (Castagnino et al, 2006). Spear growth rates over 34 ∘ C was significantly low (Watanabe et al, 2019). Moreover, traditional knowledge of producers from Peru stated that when Tmin values were under 12 ∘ C the spear production is significant less compare days with higher Tmin.…”
Section: Thermal Time and Growth Ratementioning
confidence: 95%
See 2 more Smart Citations
“…Growth rates of daily elongation of asparagus shoots increase between minimum temperatures 7-10 ∘ C to maximum of 25-30 ∘ C and when the shoot is longer (Castagnino et al, 2006). Spear growth rates over 34 ∘ C was significantly low (Watanabe et al, 2019). Moreover, traditional knowledge of producers from Peru stated that when Tmin values were under 12 ∘ C the spear production is significant less compare days with higher Tmin.…”
Section: Thermal Time and Growth Ratementioning
confidence: 95%
“…This study defined the temperature-dependent growth rate of asparagus, using two values of T b following the studies of (Wilson et al, 1999, Wilson et al, 2002. The optimum temperature for asparagus growth is 20 ∘ C (Yen et al, 1996) and its growth rate increase up 35 ∘ C (Hills, 1986;Watanabe et al, 2019). The growth rate found in Peru showed 3-4 cm day −1 the first day after emergence and 10 cm day −1 at second day after emergence of spears over the soil surface.…”
Section: Thermal Time and Growth Ratementioning
confidence: 99%
See 1 more Smart Citation
“…In addition, in terms of profitability, it is important to control the harvest timing of white asparagus; thus, studies have investigated the relationship between white asparagus sprouting and environmental conditions surrounding the crown. Heißner et al (2006) examined the effect of soil temperature on white asparagus yield, and high temperature treatments surrounding the crowns have been shown to control white asparagus sprouting (Paroussi et al, 2002;Watanabe et al, 2019). Kitazawa et al (2014) suggested that <14% O 2 in soil surrounding the crowns was effective in controlling sprouting, and sprouting inhibition was caused by the inhibition of metabolism due to the reduction in respiration in the crowns.…”
mentioning
confidence: 99%